Clinical Benefit of Evolocumab by Severity and Extent of Coronary Artery Disease: Analysis From FOURIER - Sabatine, Marc S; De Ferrari, Gaetano M; Giugliano, Robert P; Huber, Kurt; Lewis, Basil S; Ferreira, Jorge; Kuder, Julia F; Murphy, Sabina A; Wiviott, Stephen D; Kurtz, Christopher E; Honarpour, Narimon; Keech, Anthony C; et al. (Circulation (New York, N.Y.), 2018)
The FOURIER trial (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Patients With Elevated Risk) recently showed that the PCSK9 (proprotein convertase subtilisin-kexin type 9) inhibitor evolocumab significantly reduced major vascular events in patients with stable atherosclerotic cardiovascular disease, including patients with prior myocardial infarction (MI). Within the broad group of patients with prior MI, we hypothesized that readily ascertainable features would identify subsets who derive greater clinical risk reduction with evolocumab. The 22 351 patients with a prior MI were characterized on the basis of time from most recent MI, number of prior MIs, and presence of residual multivessel coronary artery disease (≥40% stenosis in ≥2 large vessels). The relative and absolute risk reductions in major vascular events, including the primary end point (cardiovascular death, MI, stroke, hospitalization for unstable angina, or coronary revascularization) and the key secondary end point (cardiovascular death, MI, or stroke), with evolocumab in these subgroups were compared. A total of 8402 patients (38%) were within 2 years of their most recent MI; 5285 patients (24%) had ≥2 prior MIs; and 5618 patients (25%) had residual multivessel coronary artery disease. In a multivariable-adjusted model that simultaneously included all 3 high-risk features and other baseline covariates, more recent MI, multiple prior MIs, and residual multivessel coronary disease remained independent predictors of cardiovascular outcomes, with adjusted hazard ratios (HRs) for the primary end point of 1.37 (95% confidence interval [CI],1.22-1.53), 1.78 (95% CI, 1.59-1.99), and 1.39 (95% CI, 1.24-1.56; all P<0.001). The relative risk reductions with evolocumab for the primary end point tended to be greater in the high-risk subgroups and were 20% (HR, 0.80; 95% CI, 0.71-0.91), 18% (HR, 0.82; 95% CI, 0.72-0.93), and 21% (HR, 0.79; 95% CI, 0.69-0.91) for those with more recent MI, multiple prior MIs, and residual multivessel coronary artery disease, whereas they were 5% (HR, 0.95; 95% CI, 0.85-1.05), 8% (HR, 0.92; 95% CI, 0.84-1.02), and 7% (HR, 0.93; 95% CI, 0.85-1.02) in those without, respectively. Given the higher baseline risk, the respective absolute risk reductions at 3 years exceeded 3% in the high-risk groups (3.4%, 3.7%, and 3.6%) versus ≈1% in the low-risk groups (0.8%, 1.3%, and 1.2%). Patients closer to their most recent MI, with multiple prior MIs, or with residual multivessel coronary artery disease are at high risk for major vascular events and experience substantial risk reductions with low-density lipoprotein cholesterol lowering with evolocumab. URL: https://www.clinicaltrials.gov . Unique identifier: NCT01764633.